2011
DOI: 10.3109/15412555.2011.560582
|View full text |Cite
|
Sign up to set email alerts
|

Airway Clearance in COPD: Need for a Breath of Fresh Air? A Systematic Review

Abstract: Studies that provide solid evidence of the effectiveness of different airway clearance techniques in patients with COPD are rather scarce. The available evidence indicates that active breathing techniques, such as active cycle of breathing techniques, autogenic drainage and forced expiration, can be effective in the treatment of COPD. The evidence for passive techniques such as postural drainage and percussion is low. Supporting techniques such as intrapulmonary percussive ventilation, positive expiratory pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 36 publications
(52 reference statements)
0
20
0
4
Order By: Relevance
“…Other PEP devices, such as TheraPEP®, have been investigated and found to be useful, but expensive, adjuncts to standard physiotherapy (Ides et al 2011, Su et al 2007. While this study set out to investigate the efficacy of such techniques, several barriers limited recruitment, resulting in a small sample and an insufficiently powered study, hence few conclusions relating to the investigated outcome measures could be made.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Other PEP devices, such as TheraPEP®, have been investigated and found to be useful, but expensive, adjuncts to standard physiotherapy (Ides et al 2011, Su et al 2007. While this study set out to investigate the efficacy of such techniques, several barriers limited recruitment, resulting in a small sample and an insufficiently powered study, hence few conclusions relating to the investigated outcome measures could be made.…”
Section: Discussionmentioning
confidence: 93%
“…In the presence of sputum plugging, PEP allows an increased volume of air to accumulate behind the sputum via collateral ventilation, moving sputum centrally towards larger airways to aid expectoration (Holland and Button 2006). It has been found to be an effective form of airway clearance for people with COPD (Ides et al 2011). Commercial PEP devices are expensive, costing between NZ$40-160; however, an alternative form of PEP that is inexpensive (costing less than $2 to make) and is used by some New Zealand and Australian physiotherapists to manage secretion clearance in COPD, is bubble-PEP (Lee et al 2008, Miller et al 2005.…”
Section: Introductionmentioning
confidence: 99%
“…1 We also found three systematic reviews, so we reviewed the bibliography of those papers looking for any clinical trial involving COPD patients. [14][15][16] This resulted in three more randomized trials (two crossover and one control group) using oscillating pressure for airway clearance. [17][18][19] These three randomized trials used outpatients.…”
Section: Related Literaturementioning
confidence: 99%
“…Ides and colleagues 59 conducted a systematic review of ACT for patients with COPD. They found that studies that provide solid evidence of the effectiveness of different ACTs in patients with COPD are scarce.…”
Section: Airway Clearancementioning
confidence: 99%